Trombositosis: Faktor Risiko Peningkatan Penyempitan Pembuluh Darah pada Petani, Buruh dan Penambak Ikan yang Merupakan Perokok Aktif di Kelurahan Tanjung Pinang Kota Palangka Raya: Thrombocytosis: Risk Factors for Increased Narrowing of Blood Vessels in Farmers, Workers and Fish Farmers Who Are Active Smokers in Tanjung Pinang Village, Palangka Raya City - Ardina, Rinny (Jurnal Surya Medika (JSM), 2019)
Active smokers are people who are smoking continuously. The population of active smokers in Central Kalimantan was 26,5% in 2013. The farmer, fish farmer, and laborer had a large proportion (44.5%) as an active smoker than another job that reported according to types of jobs. Cigarettes contain many toxic and addictive chemicals. Majority of active smokers that was living in Kelurahan Tanjung Pinang Kota Palangka Raya, especially who live in Jl. Bengaris works as a farmer, fish farmer, or laborer. Active smokers have a high risk of suffering from heart disease. Cigarette compound that harmful can cause endothelial tissue dysfunction in heart blood vessels and following by thrombus formation that due to increased platelet counts and platelet aggregation. This study aimed to describe of platelet count in active smokers in Jl. Bengaris Kelurahan Tanjung Pinang, Palangka Raya. The descriptive observational method was used in this study. The sample obtained by 48 people with purposive sampling technique with criteria such as active smokers, men, working as farmers, fish farmers, or laborers, no history of the disease, and willing to be respondent. Examination of platelet count was done by hematology analyzer. The average of respondents aged 20-30 years (35.4%) and 31-40 years (31.2%), worked as farmers (43.7%) and laborers (41.7%), duration of smoking were 1-10 year (37.5%), consumption of smoking was 11-20 cigarettes / day (41.7%), and rest periods were > 6 hours / day (64.6%). There was one person of the active smoker with a high platelet count (2.1%) and normal platelet count of 47 people (97.9%).